2018
DOI: 10.1038/s41419-018-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun-mediated microRNA-302d-3p induces RPE dedifferentiation by targeting p21Waf1/Cip1

Abstract: Dedifferentiation of retinal pigment epithelium (RPE) cells and choroidal neovascularization (CNV) contributes to the pathogenesis of age-related macular degeneration (AMD). MicroRNAs (miRNAs) have crucial roles in AMD onset and progression. We thus aim to investigate the effects of miRNAs on RPE dedifferentiation and endothelium cell (EC) behavior, and analyze its downstream pathways. We have previously identified miR-302d-3p as the most downregulated miRNA signature along with RPE differentiation. Herein, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…CDKN1A is involved in RPE differentiation, proliferation, migration, and cell-cycle progression [ 112 ]. As such, CDKN1A plays a role in the ageing process of RPE and hence in AMD [ 113 ]. SERPINA1 is serine protease inhibitor and has a role in prevention against tissue destruction [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDKN1A is involved in RPE differentiation, proliferation, migration, and cell-cycle progression [ 112 ]. As such, CDKN1A plays a role in the ageing process of RPE and hence in AMD [ 113 ]. SERPINA1 is serine protease inhibitor and has a role in prevention against tissue destruction [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unstimulated CardAP-EVs carried a higher copy number of miRNA302d-3p in comparison to cytokine stimulated CardAP-EVs, which was additionally verified by qPCR. Others have shown that this miRNA stimulated HUVECs to release more VEGF as well as to increase their tube formation capabilities in comparison to untreated controls [41]. Additionally, this group demonstrated that the pro-angiogenic potential of miRNA302-3p was abolished in inhibition experiments using siRNA and other inhibitors of the involved pathway.…”
Section: Discussionmentioning
confidence: 85%
“…For example, miR-302d-3p triggers RPE dedifferentiation by targeting p21Waf1/Cip1. 57 miR-184 promotes RPE differentiation by inhibiting the AKT2/mTOR signalling pathway. 58 miR-132 was shown to be involved in brain derived neurotrophic factor -mediated retinal axon branching via downregulation of p250GAP.…”
Section: Other Mirnasmentioning
confidence: 99%
“…The function of other miRNAs in the retina has also been studied. For example, miR‐302d‐3p triggers RPE dedifferentiation by targeting p21Waf1/Cip1 57 . miR‐184 promotes RPE differentiation by inhibiting the AKT2/mTOR signalling pathway 58 .…”
Section: Other Mirnasmentioning
confidence: 99%